LANDASAN HUKUM POSITIF PEMBERLAKUAN HUKUM ISLÂM DI INDONESIA - Eka Susylawati Eka Susylawati (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2011)
Abstract: Islamic law has been valid since a long time ago in Indonesia and it expriences dynamical effect since the era of ancient kingdom, colonialism, and post-independence. The population of Muslim is major, it reaches more  than 200 hundred millions people. This becomes sociological and functional considerations to the validity of Islamic law in Indonesia. For the shake of effectiveness, efficiency, and Muslim aspiration fulfillment, it seems feasible to adopt Islamic law as a part of public law. Indonesia is not a secular country, it is not necessary to seperate religious and statehood affairs. In advance, Islamic law has been partly adopted and it inspires the Indonesian legislation. Key Words: hukum positif, hukum Islâm, dan fiqh